Prospective Evaluation of Multinational Association of Supportive Care in Cancer Risk Index Score for Gynecologic Oncology Patients With Febrile Neutropenia. (February 2019) - Gunderson, Camille C.; Erickson, Britt K.; Wilkinson-Ryan, Ivy; Vesely, Sara K.; Leath, Charles A.; Gehrig, Paola A.; Moore, Kathleen N.
Abstract : Background: The Multinational Association of Supportive Care of Cancer (MASCC) risk-index score has been validated as a stratification tool for febrile neutropenia (FN) risk in a heterogeneous group of cancer patients; recently, it has been deemed a suitable tool in gynecologic oncology patients in a retrospective study. This is a prospective multi-institutional study wherein we sought to validate MASCC score for stratifying FN morbidity in gynecologic oncology patients. Methods: IRB approval was obtained at 4 institutions for prospective data collection of gynecologic cancer patients admitted with FN from 3/1/2013 to 9/1/2014. Participating institutions have a policy of inpatient management of FN patients receiving chemotherapy. Deidentified data was compiled and processed at the leading institution. Results: In total, 31 patients met inclusion criteria. Most had advanced stage disease (67%). 100% of patients were receiving chemotherapy (57% for primary, 43% for recurrent disease). 55% had a positive culture. Median MASCC score was 21 (range, 10 to 26); 58% of patients were considered low risk. High risk patients more often had one (11% vs. 38%, P =0.09) or multiple (6% vs. 23%, P =0.28) severe complications, ICU admission (0% vs. 15%, P =0.17), and delay in next chemotherapy cycle (33% vs. 54%, P =0.25). No patients died from FN during the study period. Conclusions: This pilot data suggests that MASCC score may be a promising tool for determining suitability of outpatient management of FN in gynecologic oncology patients. Larger studies are warranted to achieve statistically significant results, which may enable us to effectively utilize this risk stratification tool for cost containment and avoidance of nosocomial infections.